"Proceedings of the International Conference on Resource Utilisation and Intelligent Systems (INCRUIS) - 2006, January 4-6, 2006 ; Vol.2" - Veluswami (M A) Ed. (2005)
Proceedings ; International Conference ; Intelligent Systems ; INCRUIS
0
Keywords: Proceedings ; International Conference ; Intelligent Systems ; INCRUIS